Identifikasi Penerapan Circular Economy Pada Supply Chain Pangan Manihot Esculenta (Ubi Kayu) di Kabupaten Bogor - Muhamad Fadili Muhamad Fadili; Bianca Fayza Putri Rostandi; Tri Puspita Ningrum; Trian Miftakul Rohman; Eko Ruddy Cahyadi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
This research discusses the management of cassava supply chains in Bogor Regency by applying circular economy principles. The research was conducted using several methods, namely in depth interviews, primary and secondary data collection, and analysis using descriptive qualitative methods. The results showed that the application of circular economy principles in the cassava supply chain has several challenges that make the application of circular economy not yet optimal, namely limited infrastructure and technology, and lack of knowledge among stakeholders. Cassava food loss occurs at the farmer level at 11.67%-16%, the collector level at 18%, and the processor level at 40%-42% due to various factors such as size, damage, skin waste, and residual products and supporting materials. To improve the implementation of circular economy practices, it can be done by processing cassava waste into value-added products and collaboration between business actors for resource efficiency, economic and environmental sustainability.